Emerging microfluidic devices for cell lysis: a review - Nan, Lang; Jiang, Zhuangde; Wei, Xueyong (Lab on a chip, 2014)
Intracellular components containing information about genetic and disease characteristics are key substances to clinical diagnostics. Cell lysis is therefore a crucial step for efficient extraction and the subsequent analysis of intracellular components. With the advent of advanced manufacturing techniques, a number of micro systems have been proposed and applied for manipulating cells on chips. In this paper, we review emerging microfluidic devices for cell lysis. Different lysis mechanisms and related techniques are compared. The technical details, advantages, and limitations of various microfluidic devices are discussed.